The development of Neolithic pottery technology in Eastern Jazira and the Zagros Mountains - Nataliya Yu. Petrova (Documenta Praehistorica, 2019)
The origins of pottery technology in Eastern Jazira and the Zagros Mountains can be seen as a process of several stages, from unfired clay and plaster vessels to the fully ceramic technologies of the Proto-Hassuna period. This paper reviews this process and presents a technological analysis of Proto-Hassuna ceramics to investigate the relationships between the pottery traditions at sites in Eastern Jazira and the western part of the Zagros Mountains.